GRB 191016A: The onset of the forward shock and evidence of late energy injection. Issue 4 (15th February 2022) - Pereyra, M; Fraija, N; Watson, A M; Becerra, R L; Butler, N R; De Colle, F; Troja, E; Dichiara, S; Fraire-Bonilla, E; Lee, W H; Ramirez-Ruiz, E; Bloom, J S; et al.
ABSTRACT: We present optical and near-infrared (NIR) photometric observations of GRB 191016 with the COATLI, DDOTI, and RATIR ground-based telescopes over the first three nights. We present the temporal evolution of the optical afterglow and describe five different stages that were not completely characterized in previous works, mainly due to scarcity of data points to accurately fit the different components of the optical emission. After the end of the prompt gamma-ray emission, we observed the afterglow rise slowly in the optical and NIR wavelengths and peak at around T + 1450 s in all filters. This was followed by an early decay, a clear plateau from T + 5000 s to T + 11 000 s, and then a regular late decay . We also present evidence of the jet break at later times, with a temporal index in good agreement with the temporal slope obtained from X-ray observations. Although many of the features observed in the optical light curves of gamma-ray bursts are usually well explained by a reverse shock (RS) or forward shock (FS), the shallowness of the optical rise and enhanced peak emission in the GRB 191016A afterglow is not well fitted by only a FS or a RS. We propose a theoretical model which considers both of these components and combines an evolving FS with a later embedded RS and a subsequent late energy injection from the central engine activity. We use this model to successfully explain the temporal evolution of the light curves and discuss its implications on the fireball properties.